Thermal behavior and shape memory properties of PCL blends film with PVC and PMMA polymers - Pekdemir, Mustafa Ersin; Oner, Ecem; Kok, Mediha; Qader, Ibrahim Nazem (Springer, 2021)
Shape memory polymers have attracted extensive attention attributable to their characteristics and abundant applications. In this study, shape memory behavior and characterizations of poly(epsilon-caprolactone) (PCL) blended with poly(vinyl chloride) (PVC) and poly(methylmethacrylate) (PMMA) in different proportions were investigated. Some characteristics of the blended polymers, such as attenuated total reflection (ATR) infrared (IR) spectroscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), SEM, and optical microscopy (OM) were accomplished. Both melting temperature (T-m) and glass transition temperature (T-g) were affected by blending polymers. The T-m was decreased from 57 degrees C to 51 and 49 degrees C by adding 30% and 50% of PVC to PCL, respectively; moreover, adding 50% PMMA to PCL reduced the T-m of PCL to 55 degrees C. The TGA results revealed that the temperatures at which the mass of blended polymers begins to lose sharply depend on the ratio of the constituents. It is found that the PCL has a crystalline structure, while PVC and PMMA have an amorphous structure. Shape recovery was not detected in the PCL:PMMA (1:1) since the PMMA polymer did not dissolve in PCL, and therefore, it prevented the homogeneity of the blend. Besides, a shape memory recovering test was performed for PCL:PVC (7:3), whereby the blend showed an excellent strain recovery.
Keywords: ? -Caprolactone; Polyvinyl chloride; Poly(methyl methacrylate); Shape memory polymer; Blend